Efektifitas Kegiatan Kelompok Kerja Kepala Sekolah Dasar Negeri Dan Swasta Dalam Menyusun Program Kerja Di Kecamatan Lubuk Keliat Kabupaten Ogan Ilir - Widayanti, Liana; Idi, Abdullah; Iriani, Atrika (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2024)
The Effectiveness of Working Group Activities for Public and Private Elementary School Principals in Formulating Work Programs in Lubuk Keliat District, Ogan Ilir Regency. The activities serve as a platform for teachers who are part of the school cluster organization. The objective is to enhance the professionalism of teachers in order to improve the quality of education. This research is descriptive with a qualitative approach, using Organizational Effectiveness theory according to Duncan (in Zulkarnain, 2012). The results show that these activities have been effective in several aspects but have not fully achieved the goal of work program formulation. This is observed from the achievement of goals based on the vision, mission, and educational objectives, including the development of local content learning tailored to the needs of the schools, as well as the determination of minimum completeness criteria (KKM) and the education unit level curriculum standardized by the 2013 curriculum by BNSP. Challenges faced include the lack of performance and managerial competence of human resources, and the low motivation of principals which affects their knowledge in formulating curriculum work plans, thus not yet being able to improve the quality of education in the schools they lead.